Combined acquisition technique (CAT) for high-field neuroimaging with reduced RF power - Choli, Morwan; Blaimer, Martin; Breuer, Felix A.; Ehses, Philipp; Speck, Oliver; Bartsch, Andreas J.; Jakob, Peter M. (Magnetic resonance materials in physics, biology and medicine, 2013)
Clinical 3 T MRI systems are rapidly increasing and MRI systems with a static field of 7 T or even more have been installed. The RF power deposition is proportional to the square of the static magnetic field strength and is characterized by the specific absorption rate (SAR). Therefore, there exist defined safety limits to avoid heating of the patient. Here, we describe a hybrid method to significantly reduce the SAR compared to a turbo-spin-echo (TSE) sequence.